Electrophysiological Changes of Human-Induced Pluripotent Stem Cell-Derived Cardiomyocytes during Acute Hypoxia and Reoxygenation - Martta Häkli; Joose Kreutzer; Antti-Juhana Mäki; Hannu Välimäki; Reeja Maria Cherian; Pasi Kallio; Katriina Aalto-Setälä; Mari Pekkanen-Mattila (Stem Cells International)
Ischemic heart disease is the most common cardiovascular disease and a major burden for healthcare worldwide. However, its pathophysiology is still not fully understood, and human-based models for disease mechanisms and treatments are needed. Here, we used human-induced pluripotent stem cell-derived cardiomyocytes (hiPSC-CMs) to model acute ischemia-reperfusion in our novel cell culture assembly. The assembly enables exchange of oxygen partial pressure for the cells within minutes, mimicking acute ischemic event. In this study, hypoxia was induced using 0% O2 gas for three hours and reoxygenation with 19% O2 gas for 24 hours in serum- and glucose-free medium. According to electrophysiological recordings, hypoxia decreased the hiPSC-CM-beating frequency and field potential (FP) amplitude. Furthermore, FP depolarization time and propagation slowed down. Most of the electrophysiological changes reverted during reoxygenation. However, immunocytochemical staining of the hypoxic and reoxygenation samples showed that morphological changes and changes in the sarcomere structure did not revert during reoxygenation but further deteriorated. qPCR results showed no significant differences in apoptosis or stress-related genes or in the expression of glycolytic genes. In conclusion, the hiPSC-CMs reproduced many characteristic changes of adult CMs during ischemia and reperfusion, indicating their usefulness as a human-based model of acute cardiac ischemia-reperfusion.